The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5202/rei.v3i1.49
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Networks in the New Economy

Abstract: Abstract:The regulation of network industries has undergone profound transformation in the past twenty years. The regulated industry is no longer the same, being exposed to new competitive dynamics having revolutionized their industrial framework, technology and interactions with users. There also have been fundamental changes in what regulation is feasible. In an "information society" a model devised in the 19th century to set prices for monopoly infrastructures such as bridges, roads and railways no longer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
0
4
0
1
Order By: Relevance
“…Based on a literature review of related journal articles, categories for the socio-economic aspects include costs, consumers' perception, privacy, cybersecurity, and regulation that influence smart grid technologies and public acceptance [92]. Analysis revealed that majority of the literature addresses costs issues [96][97][98], cyber security [76,99,100], regulatory aspects [97,101,102], customer privacy [3,103,104], and consumers' perception [105][106][107]. Furthermore, it is recommended to acquire support from information science and engineering to devise methods for automated operational monitoring, assessment, control, and decision-making to meet social, economic and environmental needs [85].…”
Section: Socio-economic-technological Aspectmentioning
confidence: 99%
“…Based on a literature review of related journal articles, categories for the socio-economic aspects include costs, consumers' perception, privacy, cybersecurity, and regulation that influence smart grid technologies and public acceptance [92]. Analysis revealed that majority of the literature addresses costs issues [96][97][98], cyber security [76,99,100], regulatory aspects [97,101,102], customer privacy [3,103,104], and consumers' perception [105][106][107]. Furthermore, it is recommended to acquire support from information science and engineering to devise methods for automated operational monitoring, assessment, control, and decision-making to meet social, economic and environmental needs [85].…”
Section: Socio-economic-technological Aspectmentioning
confidence: 99%
“…Fourth, in a digitalized electricity sector, changes in technology occur faster than before and consumers become more heterogeneous. In these conditions, pursuing the protection of energy consumers and an efficient and sustainable organization of the sector gets more difficult and is likely to require a transformation in the way regulators approach their duties and arrange their activities (Glachant, 2012). New skills and competencies in ICT, big data and behavioural sciences are certainly a starting point, but are far from enough to manage raising complexity and uncertainty (CEER, 2019b).…”
Section: Challenges For the Organisation And Regulation Of The Sectormentioning
confidence: 99%
“…At the same time, post-reform structural changes and technological progress in the sector constantly require revisiting allocation of property rights, information asymmetry, and incentive properties of regulation in the sector (Glachant, 2012).…”
Section: Introductionmentioning
confidence: 99%